Romanian Medicine Schools as Multilingual Spaces: Challenges in New Diploma Migrations - Ioniță, Anamaria; Vlad, Monica (Íkala, Revista de Lenguaje y Cultura, 2024)
This qualitative study examines several issues on multilingualism, healthcare communication, and how linguistic diversity is managed in clinical settings. Through a survey among a group of international students enrolled in medicine programs with English as a medium of instruction at the Ovidius University in Constanta (Romania), we analyze the multilingual communication strategies and modalities they deploy in their practicum at hospital in their host country. The analysis of the results showed the importance of intensifying and extending teaching and learning of the host country’s language and culture, as well as the need for the hospital to train practitioners in linguistic and cultural diversity, and to tap into international students’ multilingual language skills. Qualitative results highlighted the characteristics of the Romanian hospital setting in general, and the hospital clinical practicum in particular, as well as the communication strategies deployed in the interactional triad of foreign student - medical staff - patient.